The Influence of Hand Washing Behaviour on Diarrhea Case in Pre-School Students of Ra Al-Aziziyah Mataram in 2019 - Indah Puspa Komalasari (Muhammadiyah International Public Health and Medicine Proceeding, 2021)
The handwashing behavior is an activity conducted by a person to clean the palm for removing microorganisms. Unclean Palm Will Likely Increase The Risk Of Diarrhea Cases. The influence of handwashing on diarrhea in pre-school students of RA Al-Aziziyah Mataram in 2019. The research design used in this study is Cross-Sectional. The sample of this research is 60 pre-school students in which the sampling technique used is purposive sampling. This research was conducted on 15 - 21 of March 2019. The instrument in collecting the data is a questionnaire. Furthermore, the data were analyzed by using the chi-square test. Based on the research result, it is found that the sing value (2-tailed) is 0.01 à It Should Be < 0,05. There is a significant influence of handwashing behavior on diarrhea cases in pre-school students of Quran Al-Aziziyah Mataram 2019. A recommendation that can be conferred to parents is that they have to teach their children to maintain handwashing behavior competently that is appropriate with the seven steps and use soap to decrease diarrhea cases on children.